Factors that affecting public awareness towards Istana Budaya as the cultural heritage in Kuala Lumpur / Suriani Nabila Ibrahim - Ibrahim, Suriani Nabila (2018)
Cultural heritage in one of the legacy of physical artifacts and also intangible attributes of the group or society that is inherited or transmitted from past generation until now. In this globalization {era, cultural heritage helps people to remember our cultural diversity, and its understanding develops mutual respect and renewed dialogue amongst different cultures This final year project was designed to study the public awareness towards Istana Budaya as the cultural heritage in Kuala Lumpur. Specifically, it sought to identify what is the major factor that affecting public awareness towards Istana Budaya as the cultural heritage. In this study, researcher was identified three independent variables which are enhance accessibility, increase knowledge and suitable environment. All of this independent variables relate with dependent variable which is public awareness. In order to accomplish this study, researcher distributed the questionnaire to 111 of respondents in order to obtain data. All of the respondents were answered this questionnaire without -any issues or problems. Awareness is a very importance issue for all marketing managers especially in the service tourism industries. The method that used by the researcher in order to analysed the data are Pearson Correlation Coefficient, Regression Analysis and also Reliability Analysis. All of this data obtained by distributing the questionnaires in Taman Tasik Titiwangsa and around Istana Budaya. Statistical Package for Social Sciences (SPSS) program to run and analysed the data. From this study, the results and findings indicted that all the independent variables which are enhance accessibility, increase knowledge and suitable environment are significant towards dependent variables which is public awareness. Hence, between all of these three independent variables, increase knowledge has resulted in to have the highest relationship with independent variable which is public awareness and also this is the major factor that affecting public awareness towards Istana Budaya as the cultural heritage in Kuala Lumpur.